Institutionalization of knowledge sharing platforms in the last three decades in Francophone Sub Saharan Africa? - (:unkn) unknown (My University, 2012)
Thème 1 Learning and collective action, WS 1.1. Knowledge flows in pluralistic research and advisory systems Thème 1 Learning and collective action, WS 1.1. Knowledge flows in pluralistic research and advisory systems
Keywords: African Research